Characterization The Optical Band Gap of Indium Tin Oxide Based On Different Thickness - Binti Muhammad Redzuan, Azmira Roziana Lai; Ali, Ahmad Hadi; Sani, Nooriskandar; Azali, Muhamad Muizzudin (Enhanced Knowledge in Sciences and Technology, 2023)
In this study, Indium tin oxide as a semiconductor is a commonly used transparent conductive oxide where it has few unique properties. However, the thickness of the indium tin oxide might result in degradation that might affect optical and electrical characterization. In this study, we will investigate how the thickness influenced the performance of indium tin oxide. The method used to deposit the ITO thin film is DC magnetron sputter technique. The principle used to characterize the optical properties, electrical properties and structural properties of indium tin oxide are UV-Vis Spectrometer, four-point probe and XRD. The optical band gap is calculated by Tauc plot equation. The results shows that thickness of ITO thin film gives a significant effect on it energy band gap.